Selected Papers from the 1st International Electronic Conference on Entomology - Kavallieratos, Nickolas G. (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This book is a Special Issue on "Selected Papers from the 1st International Electronic Conference on Entomology". It contains 1 editorial, 19 research papers and 2 review papers. The contributors come from 23 different countries around the world.